Performance and emission investigation of a four-stroke liquefied petroleum gas spark-ignition engine generator used in a Malaysian night market - Yusaf T.F.; Said M.A.; Hussein I. (2023)
The objective of this study is to investigate and compare the performance and emission characteristics of the liquefied petroleum gas (LPG)-fuelled engine generator and the conventional gasoline-fuelled engine generator. The approach involves converting a gasoline engine generator, commonly used in Malaysian night markets to generate electricity, to the LPG engine generator. A four-stroke SI single-cylinder engine is equipped with an LPG injection system with minor modifications and then tested with both LPG and gasoline fuels. A venturi mixer (carburettor) was designed and in house constructed and then installed to deliver a proper A/F ratio to the combustion chamber. The commercial computational fluid dynamics software FLUENT was used for simulation of air flow inside the mixer. The converted engine was tested at constant speed for its brake-specific fuel consumption (BSFC), efficiency, exhaust temperature, and exhaust gas emissions. The results show that the performance and emission characteristics of the LPG-fuelled engine are well suited for use in night markets. Average BSFC and average efficiency for the LPG engine over a range of loads were quite similar to those for the gasoline engine: the average BSFC was 0.95 kg/kWh for the LPG engine and 1 kg/kWh for the gasoline engine. The use of LPG as fuel in a gasoline engine causes only a slight reduction in efficiency as a 17 per cent reduction in average efficiency was recorded over the entire load range; however, the LPG engine fared better at higher loads than the gasoline engine for which only as low as a 4 per cent reduction was recorded at high loads. Emission tests seem to verify the minimal pollution products; there are significant reductions in the emission concentration results when LPG is used. Average decreases of 32 per cent for nitrogen oxide, 10 per cent for carbon dioxide, and 40 per cent for carbon monoxide were recorded. Although higher values of hydrocarbon (HC) were recorded, a 50 per cent reduction in HC was found for loads higher than 700 W. The study verified the more favourable features of LPG compared to gasoline as it is one of the best alternative fuels to gasoline for spark-ignition engine generators to solve the air pollution problem in night markets. 2010 Authors.